2016
DOI: 10.1007/s13277-016-5061-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrinβ1 modulates tumour resistance to gemcitabine and serves as an independent prognostic factor in pancreatic adenocarcinomas

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies because of its broad resistance to chemotherapy. Numerous evidence indicates that integrinβ1 is upregulated in some human cancers, and it is correlated with resistance to various therapies. However, the role of integrinβ1 in chemotherapy is not clear in pancreatic cancer. The present study evaluates the potential of integrinβ1 to predict chemoresistance and prognosis in patients and to modulate resistance to gemcitabine in PDAC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Interestingly, patients who recurred more than 12 months after initial treatment showed better survival outcomes. This observation may be due to inherent differences in tumor biology across the patient cohort, rendering different grades of tumor aggressiveness and response to treatment, as has been reported in the literature 25, 26, 27, 28…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, patients who recurred more than 12 months after initial treatment showed better survival outcomes. This observation may be due to inherent differences in tumor biology across the patient cohort, rendering different grades of tumor aggressiveness and response to treatment, as has been reported in the literature 25, 26, 27, 28…”
Section: Discussionmentioning
confidence: 89%
“…These prognostic biomarkers associate with tumor clinical stage, overall survival (OS) time, and disease-free survival (DFS) time by regulating tumor biological behavior. For example, integrin β1 modulates tumor resistance to gemcitabine and serves as an independent prognostic factor in PDAC ( 8 ). Regenerating family member proteins promote acinar-to-ductal metaplasia and act as novel diagnostic and prognostic markers in PDAC ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the expression of CD29 was significantly reduced. This integrin has been linked to gemcitabine resistance and a poor outcome in pancreatic cancer [ 35 ]. Moreover, its knockdown has been reported to inhibit cell adhesion, migration, proliferation, and metastasis of pancreatic cancer, unveiling CD29 as a potential therapeutic target [ 36 ].…”
Section: Discussionmentioning
confidence: 99%